Capital Market Financing for SMEs: A Growing Need in Emerging Asia - Shigehiro Shinozaki (Asian Development Bank (ADB), 2014)
Asia's bank-centered financial systems require the reduced supply-demand gap in lending as a core policy pillar to improve small and medium-sized enterprise (SME) access to finance. Meanwhile, the diversification of financing modalities beyond conventional bank lending is another key policy pillar to better serve various financing needs of SMEs and expand their financial accessibility. The rapid growth of emerging Asia is generating SMEs' long-term funding needs and requires robust capital markets as an alternative channel for providing their growth capital. The G20 Leaders also addressed the importance of promoting long-term financing for SMEs in the context of investment. The development of capital markets that SMEs can tap is one of the policy challenges under the pillar of diversified financing modalities, which requires more sophisticated and innovative institutional arrangements in order to respond effectively to their real needs. This paper explores the potential of capital market financing for SMEs in emerging Asia, reviewing the challenges of existing SME capital markets and assessing demands on SMEs, regulators, policy makers, market organizes, securities firms, and investors for developing an SME market, based on the findings from intensive surveys. Given the responses to the national growth strategies and the cross-cutting issues of global policy agendas such as climate change, energy efficiency, and green finance, the potential for developing the exercise equity market and the social capital market in Asia is also explored in this paper.
hdl:11540/1982
Keywords: F36; G28; G29; 330; Financial inclusion; innovative financing; long-term financing; SME capital markets; SME finance